The hydration resistance, evolution mechanism of sol-coated aluminum and its effect on mechanical properties of SiC reticulated porous ceramics. Issue 8 (1st June 2020) - Liang, Xiong; Li, Yawei; Sang, Shaobai; Wang, Qinghu; He, Zhu; Li, Benwen
Abstract: As the key component for porous media burner, the sufficient strength of SiC reticulated porous ceramics (RPCs) is necessary due to the scour of hot flue gas. However, SiC RPCs prepared with template replica method often exhibited serious oxidation and low strength when the foam was burnt out. In the present work, a sol-coated Al powder with high hydration resistance was introduced into the silicon carbide slurry to promote mullite formation in SiC skeleton, meanwhile reduce the SiC oxidation ratio of sample during the heat treatment. Firstly, the silica-sol coated Al with uniform silica-sol was successfully prepared via dip coating to improve the ability of hydration resistance of Al powder. Furthermore, sol-coated Al with spherical morphology improved rheological properties of silicon carbide slurry, including viscosity and rheological behavior. In addition, the evolution mechanism of sol-coated Al in SiC RPCs was revealed. The AlO2 (g) and AlO(g) was first formed in the system, thus significantly reducing the SiC oxidation ratio in SiC RPC. The partial pressure of AlO(g) increased with the sintering temperature, the needle-shaped mullite formed at 1300 ○ C when it dissolved in the microsilica, while lumpy mullite formed as SiC was the silica source in SiC RPCs. The addition of sol-coated Al was beneficial to optimize the microstructure of SiC skeleton, resulting in higher compressive strength of SiC RPCs.